Women scientists in the space of Soviet academic history during the 1920s–1930s - O.V. Metel (Ученые записки Казанского университета: Серия Гуманитарные науки, 2021)
The problem of women’s participation in the organization of scientific research has sparked great interest over the recent years. In this paper, the problem of “women presence” in the historical academic institutions during the 1920s–1930s is discussed based on a wide range of historical sources: office documents, statistical materials, and sources of personal origin. The position of women scientists in the “old” academic structures and new “Marxist” academies in the 1920s is analyzed. New elements in the position held by women scientists at the Institute of History of the Academy of Sciences of USSR and at the Leningrad Branch of the Institute of History of the Academy of Sciences of the USSR during the 1930s are considered. The results obtained lead to the conclusion that the active involvement of women historians in the work of the institutes of the Academy of Sciences of the USSR began only in the 1930s, when, in the context of the transformations of the “academic sector,” women acquired more stable positions in the academic field. The position of women in the Soviet historical field (in the “academic sector”) was influenced by the “conservative turn” in the middle of the 1930s, as well as by the insufficient qualifications and the difficulties in the establishing a stable system of education of historians in the USSR.